Anisotropic displacement parameters and A-B phase transition in quartz-type fepo4 - Smirnov, M.; Mazhenov, N.A.; Aliouane, N.; Saint-Gregoire, P. (Publishing House of the KarSU named after E.A.Buketov, 2012)
We present novel results on the mechanism of the a-b structural phase transition (STP) occurring in FePO4. High accuracy X-ray diffraction experiments followed by a structural analysis, allow to get precise information on the thermal disorder change on different atomic sites. The data are analyzed at the light of lattice dynamics simulation results. The rigid unit mode (RUM) approach of the dynamics simulation allows the understanding of the anisotropic displacement parameters (ADPs). Surprisingly, the role of critical fluctuations of the order parameter, in the sense of Landau and Lifshitz theory, appears not relevant in the case of this SPT and the understanding of the dynamics requires the knowledge and analysis of the microscopic details of the system
Keywords: Crystal; lattice; vibration; phonon; heat parameters